DESIGUALDADE ECONÔMICA E EDUCAÇÃO MATEMÁTICA: UMA LEITURA PLAUSÍVEL DE SIGNIFICADOS E AFETOS DE LICENCIANDOS EM MATEMÁTICA - NATÁLIA MAYUME SOARES MORIYA (2024)
The objective of this research is to investigate meanings and affects of students of a Bachelor’s Degree in Mathematics in relation to economic inequality. We held meetings with students and against the invitations, that is, situations that explain scenes of economic inequalities, we dialogue, problematize and produce about this contemporary emergency. The six meetings, with three classes of undergraduates, each with approximately 1 hour, were recorded in audio and video. These students are part of the Institutional Program of Teaching Initiation Scholarships (PIBID). The main theoretical and methodological framework of this research is the Semantic Fields Model (MCS). Talking and feeling about/with economic inequality, an emergency of the Antropocene, in the initial training of teachers, proved to be very powerful, because this type of inequality often accompanies us in classrooms and sometimes is silenced and naturalized. Among some of our meanings and affections to which we produce and were produced in the encounters with the pibidians, we built (were built, invented), between three emerging (and emergency) discussions with economic inequalities: photos as triggers of affections, between amazement and naturalization and meritocracy. These discussions were central in the processes of interactions between students. Amazement, anguish, sadness, discomfort and recognition in some situations were affections that were part of our meetings. It is urgent and necessary that these discussions are problematized in initial training processes of mathematics teachers.